2021
DOI: 10.3991/ijep.v11i3.20491
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Networks on the Development of Students’ Social Competence

Abstract: The article analyzes the possibilities which virtual social networks provide for the development of youth’s social competence. The authors analyze the results of the survey on the students’ use of virtual social networks for communication. To achieve the purpose of the research and to determine the essence and significance of social competence we used methods of analysis, synthesis and generalization of research works; the method of observation was used to identify the peculiarities of communication between yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…─ Instructor effectiveness and social role: Students expressed positive or negative attitudes toward their instructor, the quality of their instruction, and their social role in the virtual classroom. ─ Self-efficacy: This construct is referring on the prior level of knowledge, grades of entrance exams [19], computer and software skills [22], abilities in the use of social media [26]. ─ Sustainability of the online learning framework [27]: As the United Nations Sustainable Development Group notes in its August 2020 guidance note, strengthening education systems helps countries adapt to immediate challenges, such as reopening schools safely, while training them to deal with future crises.…”
Section: Structure and Conceptsmentioning
confidence: 99%
“…─ Instructor effectiveness and social role: Students expressed positive or negative attitudes toward their instructor, the quality of their instruction, and their social role in the virtual classroom. ─ Self-efficacy: This construct is referring on the prior level of knowledge, grades of entrance exams [19], computer and software skills [22], abilities in the use of social media [26]. ─ Sustainability of the online learning framework [27]: As the United Nations Sustainable Development Group notes in its August 2020 guidance note, strengthening education systems helps countries adapt to immediate challenges, such as reopening schools safely, while training them to deal with future crises.…”
Section: Structure and Conceptsmentioning
confidence: 99%
“…To our opinion, this trend can only increase over time, as the Internet occupies more and more spheres of influence and becomes one of the main sources of information. The conducted research also showed that the most frequently used social networks in the Ukrainianspeaking region are Instagram (83.1%) and Facebook (28.0%) [11]. We consider this combination quite effective from the point of view of study and recreation.…”
mentioning
confidence: 66%
“…At the same time, STEM-education can be considered an alternative learning strategy [10], and the electronic modules can be seen as alternative learning materials [11], which are given in an electronic form and provide the educational process with interactivity and multimedia [12]. As for communication and discussion of learning tasks with the help of social networking sites and educational platforms [4], in this case special attention is paid to the social competence as an ability to avoid or solve conflicts and respect the opponent's opinion [27].…”
Section: Discussionmentioning
confidence: 99%